Long COVID-19 in Children: From the Pathogenesis to the Biologically Plausible Roots of the Syndrome - Michele Piazza; Maria Di Cicco; Luca Pecoraro; Michele Ghezzi; Diego Peroni; Pasquale Comberiati (Biomolecules, 2022)
Long Coronavirus disease-19 (COVID-19) refers to the persistence of symptoms related to the infection with severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). This condition is described as persistent and can manifest in various combinations of signs and symptoms, such as fatigue, headache, dyspnea, depression, cognitive impairment, and altered perception of smells and tastes. Long COVID-19 may be due to long-term damage to different organs—such as lung, brain, kidney, and heart—caused by persisting viral-induced inflammation, immune dysregulation, autoimmunity, diffuse endothelial damage, and micro thrombosis. In this review, we discuss the potential and biologically plausible role of some vitamins, essential elements, and functional foods based on the hypothesis that an individual’s dietary status may play an important adjunctive role in protective immunity against COVID-19 and possibly against its long-term consequences.